Development of the Electrical Engineering Drawing E-Module in the Department of Electrical Engineering, Jakarta State University - Nursyahied, Imam; Priyanto, Sugeng; Syahrir, Syahrir (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to develop an electronic book-based learning media to support the teaching of electrical engineering drawing in the Department of Electrical Engineering at Universitas Negeri Jakarta. Using the Research and Development (R&D) method with the Four-D model (excluding the dissemination stage), the learning media was evaluated by material experts, media experts, and tested with students.The evaluation results show that the learning media achieved an average feasibility score of 91.1% from material experts, 85% from media experts, and 87.1% from students, all categorized as "very good." Based on these findings, the electronic book-based learning media is deemed appropriate to be used as a supplementary tool for the Electrical Engineering Drawing course. This media is expected to enhance students' learning interest through the integration of multimedia elements such as text, images, videos, and animations within a single digital platform.